Prevalence of contact allergy to metals in the European general population with a focus on nickel and piercings: the EDEN Fragrance Study - Schuttelaar, Marie L.A.; Ofenloch, Robert; Bruze, Magnus; Cazzaniga, Simone; Elsner, Peter; Gonçalo, Margarida; Naldi, Luigi; Svensson, Åke; Diepgen, Thomas L. (Contact dermatitis, 2018)
Background Studies on sensitization to metals in the general population are scarce. Objectives To determine the prevalence of sensitization to metals in the general population, and factors associated with nickel sensitization. Methods In 5 European countries (The Netherlands, Germany, Italy, Portugal and Sweden), a random sample (N = 3119) from the general population (aged 18-74 years) was patch tested and interviewed by use of a questionnaire on exposure to metals, piercing, and jewellery. Results Overall, the age-standardized prevalences of sensitization to nickel, cobalt and chromium were, respectively, 14.5%, 2.1%, and 0.8%. The highest prevalence of nickel sensitization was seen in Portugal (18.5%) and the lowest (8.3%) in Sweden. The prevalence of cobalt sensitization varied between 3.8% (The Netherlands) and 0.9% (Italy), and the prevalence of chromium sensitization varied between 1.3% (Portugal) and 0.2% (Sweden). Significant associations were observed between nickel allergy and female sex (odds ratio [OR] 5.19; 95% confidence interval [95%CI]: 3.99-6.74), past piercing use (OR 3.86; 95%CI: 2.85-5.24), and currently having ≥3 piercings (OR 5.58; 95%CI: 4.02-7.76). Conclusions The prevalence of sensitization to metals in the European general population was high, mostly because of nickel. The lowest prevalence of contact allergy to nickel and chromium observed in Sweden supports the effectiveness of long-standing regulation.